2006
DOI: 10.1002/bit.21029
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress analysis of mammalian cell suspensions for prediction of industrial centrifugation and its verification

Abstract: This article describes the use of ultra scale-down studies requiring milliliter quantities of process material to study the clarification of mammalian cell culture broths using industrial-scale continuous centrifuges during the manufacture of a monoclonal antibody for therapeutic use. Samples were pretreated in a small high-speed rotating-disc device in order to mimic the effect on the cells of shear stresses in the feed zone of the industrial scale centrifuges. The use of this feed mimic was shown to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 14 publications
1
118
0
Order By: Relevance
“…Hutchinson and co‐workers observed significant mAb fragmentation of an IgG4 molecule with increasing centrifugation shear conditions. They hypothesized that the mechanical forces in the centrifuge were responsible for reducing the molecule into half‐antibodies (Hutchinson et al, 2006). Trexler‐Schmidt and co‐workers further demonstrated that antibody disulfide reduction can be attributed to the cell lysis and the release of intra‐cellular reducing enzymes (primarily thio‐redoxin reductase/thioredoxin) as a result of harsh centrifugation conditions (Trexler‐Schmidt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hutchinson and co‐workers observed significant mAb fragmentation of an IgG4 molecule with increasing centrifugation shear conditions. They hypothesized that the mechanical forces in the centrifuge were responsible for reducing the molecule into half‐antibodies (Hutchinson et al, 2006). Trexler‐Schmidt and co‐workers further demonstrated that antibody disulfide reduction can be attributed to the cell lysis and the release of intra‐cellular reducing enzymes (primarily thio‐redoxin reductase/thioredoxin) as a result of harsh centrifugation conditions (Trexler‐Schmidt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The use of a rotating disk shear device to mimic the shear conditions experienced during bioprocessing has been previously described (Hutchinson et al, 2006;Levy et al, 1999;Zhang et al, 2007). Here, shearing was performed in a device consisting of a single rotating stainless steel disk (diameter 40 mm, thickness 0.14 mm) mounted centrally in a 20-mL capacity stainless steel cylindrical chamber (diameter 50 mm).…”
Section: Rotating Disk Shear Device Operationmentioning
confidence: 99%
“…The disk rotation speed within the device has been previously characterized using computational fluid dynamics (CFD) in terms of the resulting maximum energy dissipation rate (Boychyn et al, 2004), a general parameter for which estimates exist for many largescale equipment designs (Yim and Shamlou, 2000). In particular, verification studies using shear sensitive material have shown a good correlation between the shear effects of the feed-zone of large-scale centrifuge designs and the rotating disk mimic (Boychyn et al, 2004;Hutchinson et al, 2006). In this study, the disk device was operated at rotation speeds of 300, 400, 467, 500, and 533 revolutions per second (rps).…”
Section: Rotating Disk Shear Device Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques can account for up to 25% COG/g when factors such as capital cost and energy consumption are included (Marichal‐Gallardo and Álvarez, 2012). Primary processing of high cell density feed streams requires particular consideration to avoid cell stresses and shearing that could result in protein aggregation and cell lysis (Hutchinson et al, 2006; Kiese et al, 2008). The latter affects the quantity and quality of product through the release of host cell proteins (HCP), proteases, and DNA (Sandberg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%